O DIREITO À EDUCAÇÃO EM RISCO: a influência dos “sem partido” e dos “sem escola” na legislação educacional brasileira - Simone de Fátima Flach (Universidade Federal do Maranhão, 2019)
Under the light of historical and dialectical materialism, the text aims to present conjunctural elements of contemporary Brazilian educational policy and to present evidence that the right to education is at risk. Therefore, it presents some elements related to Brazilian social and political reality, the main constitutional and infraconstitutional forecasts that (still) guarantee the right to education in Brazil, and finally some proposals for legislative amendment, especially the "School without party" and "Homeschooling", which can collaborate for a regression in the educational offer, mainly when destined to the working class.